CONCERNS FOR THE POORLY OFF IN ORDERING RISKY PROSPECTS. (November 2015) - Bovens, Luc
Abstract: The Distribution View provides a model that integrates four distributional concerns in the evaluation of risky prospects. Starting from these concerns, we can generate an ordering over a set of risky prospects, or, starting from an ordering, we can extract a characterization of the underlying distributional concerns. Separability of States and/or Persons for multiple-person risky prospects, for single-person risky prospects and for multiple-person certain prospects are discussed within the model. The Distribution View sheds light on public health policies and provides a framework for the discussion of Parfit's Priority View for risky prospects.